Angelman Syndrome: Molecular Cytogenetic Studies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Clinical, neurological, and molecular genetic studies of 22 patients with diagnostic features of Angelman syndrome (AS) are reported from National Taiwan University Hospital, Taipei.